Punctual mutations in lipoxygenase sequence expressed in black soybean seed coat - Mertz,Liliane Marcia (2013)
Lipoxygenase enzymes are relevant in several characteristics of soybean seeds, such as germination performance, storage capacity and tolerance to infection by microorganisms. In this sense, the study of allelic variations of the genes related to that enzyme may be promising for the development of molecular markers associated with phenotypic characteristics which are relevant to seed physiology. This study aimed to identify mutations in lipoxygenase sequence expressed in black soybean seed coat. After isolation of the sequence of interest by the cDNA-AFLP technique, such sequence was compared with sequences of nucleotides and proteins of the lipoxygenase present in yellow soybean seed coat. Analysis of multiple sequence alignment has shown an expressive number of changes in the sequence of nucleotides, which have resulted in the modification of 13 amino acids in the translated protein. The identification of such mutations widens the possibility for further studies involving the association of these allelic variations with phenotypic differences of interest to seeds physiology.